Mycoplasma pneumoniae-Induced-Stevens Johnson Syndrome: Rare Occurrence in an Adult Patient - Samad Rasul; Faria Farhat; Yared Endailalu; Fatima Tabassum Khan; Vishal Poddar (Case Reports in Medicine, 2012)
Stevens-Johnson syndrome (SJS) is an uncommon occurrence in Mycoplasma pneumoniae (M. pneumoniae) infection (1–5%) and has been mainly reported in children and young adults. We present a case of SJS in a 32-year-old male induced by M. pneumoniae infection. This patient presented with fever, cough, and massive occupation of mucus membranes with swelling, erythema, and necrosis accompanied by a generalized cutaneous rash. He clinically responded after treatment with antibiotics and IVIG. SJS is usually a drug-induced condition; however, M. pneumoniae is the commonest infectious cause and should be considered in the differential diagnosis.